Determinants of Employee Performance with Mediation of Work Discipline at PT. Tangguh Samudera Jaya - Larasati, Annita Dyah; Edalmen, Edalmen (International journal of economic perspectives, 2025)
The purpose of this study was to determine the influence of leadership style, organizational culture, and individual characteristics on employee performance, mediated by work discipline at PT. Tangguh Samudera Jaya. The sample for this study consisted of all 106 employees of PT. Tangguh Samudera Jaya. The results indicate that leadership style, organizational culture, and individual characteristics have a positive and significant effect on employee performance, with work discipline serving as a mediating variable that strengthens this relationship.